Analisis Kualitatif Peran Guru sebagai Motivator dalam Meningkatkan Minat Belajar Siswa di MA Hidayatulah Qomariyah Kota Bengkulu - Ikke Wulan Dari; Ika Elsa Junita; Maya Ramadani; Soleha Elza Aulia (Universitas Muhammadiyah Gresik, 2025)
This research aims to analyze the role of teachers as motivators in increasing students' interest in learning at MA Hidayatul Qomariyah, Bengkulu City. The research method used is qualitative with a descriptive approach. Data was collected through observation, interviews and documentation. The research results show that teachers have an important role in providing motivation to students through various strategies, such as giving awards, personal approaches, and using innovative learning methods. Factors that support the effectiveness of the teacher's role as a motivator include good communication, availability of learning facilities, and support from the school environment and family. These findings provide insight for educators and stakeholders in efforts to improve the quality of education by strengthening the role of teachers as motivators.